PENGARUH PERMAINAN SIMAK-ULANG UCAP TERHADAP KEMAMPUAN MENYIMAK ANAK USIA 4-5 TAHUN DI RA AS-SYAFI’IYAH KOTA MEDAN T.A 2018/2019 - Cynthia Fitri Kautsar; Masganti Sit; Ramadhan Lubis (Universitas Islam Negeri Sumatera Utara, 2019)
This reasearch is meant to find out: 1) the influence of the see-repeat speech game on children's listening abilities; 2) the influence of the method of storytelling on children's listening abilities; 3) the difference in the influence of the see-repeat speech game with the method of storytelling on children's listening abilities aged 4-5 years in RA As-Syafi'iyah. This research is a quantitative study, a type of Quasi Experiment design research. The population is 22 children. Sampling in this study uses a simple random sampling technique. The results of this study are: 1) The influence of the see-repeat speech game on children's listening abilities, as evidenced by the average test score of 6.6 to 15.3; 2) the the influence of the method of storytelling on children's listening abilities, as evidenced by the average test score of 5.0 to 10.7, amounting to 11 children; 3) there is a difference in the influence between the see-repeat speech game with the method of storytelling on the ability to listen to children aged 4-5 years in RA As-Syafi'iyah seen from the tcount = 14.0988> ttable = 2.086.